Microencapsulação de suco de laranja (Citrus sinensis) e colágeno hidrolisado por gelificação iônica - Reis, Aline Andrade (2021)
The growing concern of consumers with quality of life has driven the search for healthy foods and/or ingredients. One of these ingredients is collagen, and Vitamin C is essential for its synthesis as it acts in the hydrolyzing reaction of proline and lysine, amino acids responsible for the structure and function of collagen, contributing to the improvement of the skin's characteristics. Given the above, the aim of this study was to obtain microcapsules of orange juice and collagen hydrolyzed by ionic gelation, aiming at the elaboration of a product with conservation of bioactive compounds and amino acids. To obtain the microcapsules, two ionic gelling processes were performed using two different gelling agents: sodium alginate and agar agar. The microcapsules were prepared in two formulations: orange juice microcapsules with hydrolyzed collagen and sodium alginate gelling agent and orange juice microcapsules with hydrolyzed collagen and agar gelling agent. The microcapsules were stored at 5 ± 2°C for 16 days, analyzing color, TSS, pH, ATT, total proteins, glycine, hydroxyproline, proline, bioactive compounds and antioxidant capacity (DPPH, ABTS and FRAP). The analyzes were performed in triplicate with the data analyzed by ANOVA and the means compared using the Tukey test at a 5% significance level. During storage, the Vitamin C contents of SAL and SAG microcapsules showed significant divergence (p ≤ 0.05) in relation to time and treatments applied. The glycine contents of the SAL and SAG microcapsules statistically disagreed (p ≤ 0.05) with each other and in relation to time, with an increase in the contents until the end of storage. In the quantification of Hydroxyproline, the SAL and SAG samples showed a significant difference (p ≤ 0.05) between them, however in relation to time there was no significant divergence (p ≤ 0.05). In the Proline parameter, a significant difference was observed between treatments and times applied (p ≤ 0.05), and the SAG microcapsule presented much higher contents. With the data shown in this study, it can be concluded that the addition of hydrolyzed collagen and orange juice in the preparation of microcapsules enhances the protein, bioactive and antioxidant properties and enables the reduction in the use of synthetic antioxidants, making them an innovative product.